If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 22 + -9x Solving 4 = 22 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 4 + 9x = 22 + -9x + 9x Combine like terms: -9x + 9x = 0 4 + 9x = 22 + 0 4 + 9x = 22 Add '-4' to each side of the equation. 4 + -4 + 9x = 22 + -4 Combine like terms: 4 + -4 = 0 0 + 9x = 22 + -4 9x = 22 + -4 Combine like terms: 22 + -4 = 18 9x = 18 Divide each side by '9'. x = 2 Simplifying x = 2
| 5+11= | | x^2+28x=-192 | | f(x)=x^3-6x^2+9x+15 | | 12-(7-x)=45 | | y=-2x^2+12x-14 | | f(x)=5xln(9x)-5x | | 21+4(9-5)= | | x=0.95(x+y) | | -18-1+25+36=-3-4m-6+5m | | 42*22= | | 4x-5+7=2x+8 | | 1+4(x+7)=-19 | | (42)3.14= | | 2*3.28571429-10/7= | | (s)(-3st)(.3)= | | 2*23-10/-7= | | |6-24|*(-2)/(-2)= | | 2*23/7-10/-7= | | 10000(7.39q+14.77)=1000(3.95-4.21q) | | n(n-1)/2 | | 6(6y-1)-16=2(3y-1)-24 | | 5(v-5)-7v=-13 | | 8(u+3)-6u=12 | | (-1/2)= | | in(3x-2)=in(x)+in(7) | | 0.3(600-2.2x)=3.6(2x-3000) | | 0.3(6000-2.2x)=3.6(2x-3000) | | 3(2-x)+4=3x-2(2x+3) | | (0.1)*(0.1)= | | 7.3x-2.4(x-1)=7.9 | | -19=7(w+3)+3w | | 7.3-2.4(x-1)=7.9 |